Análise da fadiga muscular associada com a movimentação periódica de membros inferiores durante o sono em pacientes com sequelas motoras de poliomielite - Oliveira, Adriano Rodrigues de (2010)
Neurophysiological abnormalities may occur during sleep, such as periodic motion of the lower limbs, resulting in worsening of muscle fatigue, contributing to several complications such as Post Polio Syndrome. These changes affect the normal activity of skeletal muscles and in combination with other relevant events related to the sequelae of poliomyelitis, may influence physical inactivity in this population. To contribute to our understanding of neurophysiological abnormalities, the primary objective of this study was to analyze and correlate these complications with surface electromyography (EMG) before, during and after analysis of polysomnography data, associating fatigue with the periodic motion of the lower limbs and to characterize the other changes that occur during sleep in this population. For the sample we adopted the statistical calculation, resulting in 19 subjects with sequelae of poliomyelitis, which were tested for peripheral muscle strength, reflexes monosynaptic and analysis of sleep disorders. Thus, the thesis outlined in Article I the neurophysiological and the behavioral changes that occurred during sleep of the polysomnography volunteers, creating a specific profile that may contribute to the understanding of muscle fatigue, which is a common complaint of patients. In this first analysis set out in Article I, lower sleep efficiency was observed, which can be credited by the periodic motion of the lower limbs and by episodes of apnea and hypopnea, which led to higher rates of arousals and awakenings. With these responses, we aimed in Article II a way to assess the neurophysiological changes through EMG, using the median frequency (MF) and the amplitude of electromyographic signals for evidence of muscle fatigue of the rectus femoris. Besides that, in the same article it was used the onset of achilles and patellar reflexes to corroborate the findings of MF, where it pointed to a slowing in the period after sleep, but was not statistically significant. However, when analyzing the peripheral muscle strength, the presence of muscle fatigue was observed, showing a statistically significant difference (p <0.05). Muscle fatigue was associated with sleep disorders and more objectively, with the movements of the lower limbs. Being fatigue a disabling factor and commonly found in after poliomyelitis patients, our results may reflect as a functional or prognostic marker, however, more studies are needed to reach this goal.